Marble Powder As Fine Aggregates in Concrete - Memon, M. J.; Jhatial, A. A.; Rid, Z. A.; Rind, T. A.; Sandhu, A. R. (Engineering, Technology & Applied Science Research, 2019)
Marble industry contributes significantly to the socio-economic development of any country. Due to the abundance of marble reserves, Pakistan relies on marble industry, which in turn contributes to its GDP. Marble powder (MP), produced from the marble industry is also increasing, which constantly remains a source of hazards to the environment. At the same time, natural sand deposits are decreasing, causing an acute need for a product that matches the properties of sand in concrete. This study has been conducted to demonstrate the possibility of using MP as a replacement of sand in the manufacturing of concrete. The MP was used in 5 different dosage percentages ranging from 0% to 100% by weight of sand with an increment of 25%. The effect of MP on the strength behavior of concrete was studied at three different curing ages (7, 14 and 28 days). It was observed from the results that MP could potentially replace sand up to a certain limit without compromising on strength. It was also noticed that 50% sand replacement with MP was optimum at which 13.52% and 35.54% increase in compressive and flexural strength was achieved compared to the control sample. Based on the results of this experimental study, it is clear that MP can partially be used in place of sand in concrete.